Two-dimensional filters and filter banks - Srinivasa Gopalan Shyamsunder. (2010)
The applications for the perfect reconstruction filter banks have been found in many areas of digital signal processing theory. In this dissertation, we have dealt with the design of filter bank for 1D case and also for the 2D non-separable case. We have used lifting based factorization for designing the filter banks based on its advantages like computational efficiency, memory savings, integer-to-integer transform, no boundary extension and parallel processing. In this dissertation, an extensive study is made from the basics of multirate system till the end design of the filter bank including the lifting scheme. This report deals with 2-channel design, for both one dimension and two dimensions. By applying lifting structure, we have studied the effectiveness of this structure in the design of filter bank. This idea can also be implemented for M-channel case.